Peranan Citizen Journalism di Media Online - Kamil Dwimuzakkii; Yadi Supriadi (UNISBA Press, 2022)
Abstract. Along with the times, the media has also experienced a very large development so that the emergence of the internet as a change that can provide information to the public more quickly. Then came the term Citizen Journalism or Citizen Journalism, which is the latest breakthrough from the world of journalism. Citizen Journalism has the initiative to carry out journalistic activities as a way to convey their aspirations to the public through the media. Especially with the development of technology, online media has emerged which can be said to be new media. This online media is currently often used by audiences, especially online journalists. Because it is from online media that all the information obtained will be very easy to access by anyone, anytime and anywhere. Therefore, it is not surprising that at this time Citizen Journalism is also busy in obtaining information like journalists in general. The purpose of this study was to determine the role of Citizen Journalism in the online media Galamedianews.com in providing information then to find out how important Citizen Journalism is in the online media Galamedianews.com and to find out how Citizen Journalism works in obtaining information. The method used by this researcher is a qualitative method, with a case study approach. The researcher chose this method because he wanted to find out more about the role of Citizen Journalism in the online media Galamedianews.com by collecting the data used in the research from the results of interviews, observations, documentation, and literature study. The results of the study are, 1) The role of Citizen Journalism can be said to be important by Galamedianews.com because it always provides information through online media even though most of them send articles. 2) In obtaining the facts, Citizen Journalism conducts mentions on social media Galamedianews.com. 3) Galamedianews.com will check the correctness of the results of mentions from Citizen Journalism which will later be made into news. Abstrak. Seiring dengan perkembangannya zaman, media pun mengalami perkembangan yang sangat besar sehingga munculnya internet sebagai salah satu perubahan yang dapat memberikan informasi lebih cepat tersampaikan kepada masyarakat. Kemudian hadirlah istilah Citizen Journalism atau jurnalisme warga yang merupakan suatu terobosan terbaru dari dunia jurnalistik. Citizen Journalism berinisiatif untuk melakukan kegiatan jurnalistik sebagai cara untuk menyampaikan aspirasi mereka kepada khalayak melalui media. Terlebih dengan perkembangan teknologi, munculah media online yang dapat dikatakan sebagai new media (media baru). Media online inilah yang saat ini sering digunakan oleh para khalayak, khususnya para jurnalistik online. Karena dari media online lah segala informasi yang didapat akan sangat mudah di akses oleh siapa saja, kapan saja, dan dimana saja. Maka dari itu tidak heran jika pada saat ini Citizen Journalism pun ikut ramai dalam memperoleh informasi seperti layaknya para jurnalis pada umumnya. Tujuan dari penelitian ini adalah untuk mengetahui peranan Citizen Journalism di dalam media online Galamedianews.com dalam memberikan informasi kemudian untuk mengetahui seberapa pentingnya Citizen Journalism di media online Galamedianews.com dan untuk mengetahui cara kerja Citizen Journalism dalam mendapatkan informasi. Metode yang digunakan oleh peneliti ini adalah metode kualitatif, dengan pendekatan studi kasus. Peneliti memilih metode ini karena ingin mencari tahu lebih jauh mengenai peranan Citizen Journalism di media online Galamedianews.com dengan cara pengumpulan data yang digunakan di dalam penelitian dari hasil wawancara, observasi, dokumentasi, dan studi kepustakaan. Hasil penelitian adalah, 1) Peranan Citizen Journalism dapat dikatakan penting oleh pihak Galamedianews.com karena selalu memberikan informasi melalui media online meskipun kebanyakanna mengirimkan artikel. 2) Dalam memperoleh faktanya, Citizen Journalism melakukan proses mentions terhadap media social Galamedianews.com. 3) Pihak Galamedianews.com akan mengecek kebenaran hasil mentions dari Citizen Journalism yang nantinya akan dijadikan sebuah berita.